Study of Value Co-Creation, In Pergiramerame Tour & Travel Service Development Strategy Using the Dart Model - Bagus Setiawan; Sudarmiatin; Agus Hermawan; Purwiyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
One of the most effective digital marketing strategies today is co-creation marketing. Co-creation places consumers as parties who actively share to create value or products. This study aims to determine the form of value co-creation in Pergiramame Tour & Travel with the DART model (Dialogue, Access, Risk Assessment, Transparency) as a strategy in innovation and product development while evaluating value co-creation in Pergiramame Tour & Travel with the DART model. . The results of the study show that Pergiramame Tour & Travel has been very good at applying the DART concept to create corporate image and value. Although some things can be maximized again, each model makes a positive contribution and is believed to be able to contribute sustainably in strengthening the company, especially in the current era of society 5.0. Pergiramame Tour & Travel has been very good at implementing the DART concept to create a corporate image and value. Although some things can be maximized again, each model makes a positive contribution and is believed to be able to contribute sustainably in strengthening the company, especially in the current era of society 5.0